PENGARUH SUB KULTUR DAN KONSENTRASI FOSFAT ANORGANIK TERHADAP KESTABILAN PRODUKSI PENISILIN G ASILASE (PGA) DAN PROTEASE EKSTRASEL OLEH BACILLUS SUBTILIS BAC4 - Sinaga, Rita
Penicillin G acylase is an enzyme which is important for penicillin derivative ?-laktam synthesis. This enzyme can hydrolize penicillin G or penicillin V into 6-aminopenicillanic acid, a starting material for production of semi-synthetic antibiotics. Commercially, PGA is produced intracellularly from Escherichia coli, which means the process needs cell wall disruption. Therefore, many scientist try to look for other microorganisms which can produce PGA extracellularly. It is known that Bacillus subtilis BAC4 can produce PGA extracellularly, although the enzyme is not stable since protease can also be produced at the same time. This instability was investigated by studying the influence of bacteria sub culture in LuriaÂ–Bertani (LB) medium in 0, 2, and 4 weeks and influence of concentration inorganic phosphate (6, 12, 18, 24) gram/L in the growth medium. Growth curve was investigated by measuring bacterium cell concentration at the optical density 600 nm. PGA and protease activity was investigated by Kornfeld and Horikoshi method, respectively. Growth curve of bacteria resulted from the tenth sub culture without storage, showed that the growth is 0,3 Unit/L. The lowest protease activity was achieved in this condition. In this condition, the present of 24 gram/L inorganic phosphate could increase the PGA activity until 0,8 Unit/L although the growth of bacteria is relatively low. We can conclude that the best condition for PGA production by Bacillus subtilis BAC4 is the tenth sub culture without storage, added by inorganic phosphate 24 gram/L in the growth medium 0,8 Unit/L.